2022
DOI: 10.7759/cureus.28589
|View full text |Cite
|
Sign up to set email alerts
|

Provider’s Perception of Parental Anxiety in the Pediatric Intensive Unit

Abstract: Parents of critically ill children in the Pediatric Intensive Care Unit (PICU) commonly experience new or worsening anxiety, which can lead to long-term sequelae in the form of post-traumatic stress disorder (PTSD). To investigate how well the PICU providers recognize and assess parental anxiety, we assessed the acute and baseline anxiety level of 30 parents in the PICU with the State-Trait Anxiety Inventory (STAI) and compared the results with the PICU physician's and nurses' assessments. All but four parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Consensus on outcome measures is growing (29) and the recent research on risk factors for poorer psychological outcomes (30–32) has identified several potentially useful screening instruments that could be used with families while the child is still in hospital. This is important because although the implicit assumption is that PICU staff refers those families in the greatest distress, recent research suggests that staff may not always judge levels of parental anxiety accurately (33). Recent research has also demonstrated that parental PTSD can impact child PTSD (34) and quality of life (35) over time.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus on outcome measures is growing (29) and the recent research on risk factors for poorer psychological outcomes (30–32) has identified several potentially useful screening instruments that could be used with families while the child is still in hospital. This is important because although the implicit assumption is that PICU staff refers those families in the greatest distress, recent research suggests that staff may not always judge levels of parental anxiety accurately (33). Recent research has also demonstrated that parental PTSD can impact child PTSD (34) and quality of life (35) over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PFCC also has an impact on the psychological response of parents. According to Aljabari et al (2022), parental involvement in childcare can reduce anxiety in parents. Parental involvement in care will provide opportunities for them to care for their children directly, receive information on their children's health conditions, and improve relationships with care providers (McCabe, 2014).…”
Section: Discussionmentioning
confidence: 99%